Methods of Analysis of Macroalae Associations in Seagrass Ecosystems on Sibu Island, North Oba District, Tidore Islands City - H. Fadel, Ariyati; Subur, Riyadi; Abubakar, Salim; Alhadad, M.Said; Serosero, Rugaya; Rina, Rina; Abdulkadir, Masykur; Abubakar, Yuyun; Muksin, Darmiyati (Agrikan Jurnal Agribisnis Perikanan, 2023)
The association between macroalgae and seagrasses has many very important ecological functions, namely as a nurturing and foraging area for various types of marine organizations and to maintain the preservation and balance of marine diversity. Various types of fish that have important economic value use the habitat for shelter and foraging. The methods used in this study are is the descriptive method, the descriptive method is knowing the existence of independent variables or survive either on one or more variables. The data obtained is displayed in the form of tables or figures. Type description based on the results of sampling in the field found 11 types of macroalgae, namely Turbinaria ornate, Turbinaria conoides, Sargassum cristaefolium, Sargassum polycystum, Sargassum muticum, Padina australis, Dictyota pinnatifida, Halimeda macroloba, Bornetella oligospora, Eucheuma denticulatum, and Chondrus crispus. Of the 11 types of macroalgae there are 8 species of macroalgae that live in sand substrate, 6 species live in muddy sand substrate, 1 species live in mud substrate, 4 species live in sandy mud substrate, 9 species live in coral substrate or coral faults, and 6 species live in rock substrate.